Primary Caregivers of Children Affected by Disorders of Sex Development: Mental Health and Caregiver Characteristics in the Context of Genital Ambiguity and Genitoplasty. (16th May 2010) - Fedele, David A.; Kirk, Katherine; Wolfe-Christensen, Cortney; Phillips, Timothy M.; Mazur, Tom; Mullins, Larry L.; Chernausek, Steven D.; Wisniewski, Amy B.
Abstract : Purpose . To determine the relationship between having a child with a DSD including ambiguous external genitalia, as well as the decision of whether or not to have early genitoplasty for that child, on the mental health and parenting characteristics of caregivers. Materials and Methods . Caregivers were recruited from centers that specialize in DSD medicine and completed the Beck Depression Inventory 2nd Edition (BDI-2), Beck Anxiety Index (BAI), Parent Protection Scale (PPS), Child Vulnerability Scale (CVS) and Parenting Stress Index/Short Form (PSI/SF). Results and Conclusions . Sixty-eight caregivers provided informed consent and completed the study. Among female caregivers whose children never received genitoplasty, greater parenting stress was reported( F ( 1, 40 ) = 5.08,     p = .03 ) . For male caregivers, those whose children received genitoplasty within the first year of life reported more overprotective parenting and parenting stress than those whose children received genitoplasty later than 12 months of age( F ( 1, 13 ) = 6.16,     p = 0.28 ) ;F ( 1, 15 ) = 6.70,     p = .021 ), respectively).